Religion, ethnicity, and male pronatalism in selected municipalities in the poorest provinces in the Philippines - Aniban, Marian C. (Population Institute, University of the Philippines Diliman, 2011)
This study explores currently married males' pronatalism in selected municipalities in the poorest provinces in the Philippines. Pronatalism is defined as a view or value that is supportive of procreation and is therefore against limiting reproduction. Using the Individual Man's data of 2006 UNFPA 6th Country Programme Baseline Survey, the study combined the variables for the desired number of children, approval of family planning, and contraceptive use to come up with a single measure of the index of pronatalism. Since the data consists of selected municipalities in selected provinces, the results generated from this research do not represent the total population of currently married males in the Philippines. Results of the study show that the level of pronatalism increase with increasing years of age. Pronatalism is lower among males with higher education and among respondents who are working and whose wives/partners are also working. Compared to Catholics and adherents of other religions, Muslim males have higher levels of pronatalism. Moreover, a substantial variation in pronatalism is seen among various ethnic groups in the sample. Such findings are important in understanding male fertility, particularly their orientation towards large families, as male partners are also known t influence women's fertility preferences.